Incremental Value of Aortomitral Continuity Calcification for Risk Assessment after Transcatheter Aortic Valve Replacement - Willemink, Martin J. (Radiol Cardiothorac Imaging, 2019)
PURPOSE: To investigate the association of aortomitral continuity calcification (AMCC) with all-cause mortality, postprocedural paravalvular leak (PVL), and prolonged hospital stay in patients undergoing transcatheter aortic valve replacement (TAVR). MATERIALS AND METHODS: The authors retrospectively evaluated 329 patients who underwent TAVR between March 2013 and March 2016. AMCC, aortic valve calcification (AVC), and coronary artery calcification (CAC) were quantified by using preprocedural CT. Pre-procedural Society of Thoracic Surgeons (STS) score was recorded. Associations between baseline AMCC, AVC, and CAC and 1-year mortality, PVL, and hospital stay longer than 7 days were analyzed. RESULTS: The median follow-up was 415 days (interquartiles, 344–727 days). After 1 year, 46 of the 329 patients (14%) died and 52 (16%) were hospitalized for more than 7 days. Of the 326 patients who underwent postprocedural echocardiography, 147 (45%) had postprocedural PVL. The CAC score (hazard ratio: 1.11 per 500 points) and AMCC mass (hazard ratio: 1.13 per 500 mg) were associated with 1-year mortality. AVC mass (odds ratio: 1.93 per 100 mg) was associated with postprocedural PVL. Only the STS score was associated with prolonged hospital stay (odds ratio: 1.19 per point). CONCLUSION: AMCC is associated with mortality within 1 year after TAVR and substantially improves individual risk classification when added to a model consisting of STS score and AVC mass only. Supplemental material is available for this article. © RSNA, 2019 See also the commentary by Brown and Leipsic in this issue.